Allometric relationships of the clam Marcia opima (Gmelin, 1791), collected - Suja, N; Muthiah, P (Indian Journal of Fisheries, 2011)
The relationship between various morphological attributes such as shell-on weight, length, width, height, wet meat weightand dry meat weight of the baby clam,Marcia opima was studied from two longitudinally separated localities viz., TuticorinBay along the south-east coast and Ashtamudi Lake along the south-west coast of India. Using the equation, W= aLb, therelationship between length and shell-on weight was established. The relation between a part and the whole body or betweenparts of a growing animal is described by the general equation Y= a+bX. The slope values of the length - weight relationshipof the baby clam followed the cube law. It was also observed that true allometric relationships exist between weights andlinear measurements. The values of correlation coefficient for different morphological relationships were very close to unity.Length is found to be the most useful parameter to predict other biomass parameters from field study.